2013
DOI: 10.1364/oe.21.001713
|View full text |Cite
|
Sign up to set email alerts
|

Optical absorption enhancement of hybrid-plasmonic-based metal-semiconductor-metal photodetector incorporating metal nanogratings and embedded metal nanoparticles

Abstract: We propose and numerically demonstrate a high absorption hybrid-plasmonic-based metal semiconductor metal photodetector (MSM-PD) comprising metal nanogratings, a subwavelength slit and amorphous silicon or germanium embedded metal nanoparticles (NPs). Simulation results show that by optimizing the metal nanograting parameters, the subwavelength slit and the embedded metal NPs, a 1.3 order of magnitude increase in electric field is attained, leading to 28-fold absorption enhancement, in comparison with conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…From literature, Tan et al [1] have reported 1.5 LAEF with single nanogratings based plasmonic PD using gold material. Tan et al [14] have presented 1.2 LAEF with double gratings based photodetector using gold material at 900 nm top rst grating width and also proposed the high absorption device by embedding metal nanoparticles with nanogratings [15]. Masouleh et al [16] have obtained 1.56 LAEF at 1.4 µm using gold material for nanogratings with 450 nm SWA width and also compared the different plasmonic nanogratings pro le to enhance the light absorption in nanostructured device [17].…”
Section: Introductionmentioning
confidence: 99%
“…From literature, Tan et al [1] have reported 1.5 LAEF with single nanogratings based plasmonic PD using gold material. Tan et al [14] have presented 1.2 LAEF with double gratings based photodetector using gold material at 900 nm top rst grating width and also proposed the high absorption device by embedding metal nanoparticles with nanogratings [15]. Masouleh et al [16] have obtained 1.56 LAEF at 1.4 µm using gold material for nanogratings with 450 nm SWA width and also compared the different plasmonic nanogratings pro le to enhance the light absorption in nanostructured device [17].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the elliptical nanograting increases the light transmission [22]. In some recent references, for enhancing absorption in the GaAs layer, either nanoparticles or nanowires are used to excite localized surface plasmon resonances [22,23]. In our previous work [24], we used the hybrid plasmonic effect to confine more light in the active layer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in another study, it was suggested that instead of using a binary diffraction grating structure, the structure that uses the second diffraction grating layers of nanoparticles became operative [6]. The Plasmonic radiation in these NPs leads to improve the absorption coefficient.…”
Section: Introductionmentioning
confidence: 99%